Evaluating effects of prenatal exposure to phthalates on neonatal birth weight: Structural equation model approaches. (August 2018) - Song, Qi; Li, Ruzhi; Zhao, Yan; Zhu, Qingyang; Xia, Bin; Chen, Shangqin; Zhang, Yunhui
Abstract: Background: A large body of evidence has shown that phthalate exposure can lower birth weight in animals and human beings. However, there are only limited data on whether phthalates could affect birth weight directly or indirectly through gestational age and pregnancy syndrome. Objectives: To evaluate the effects of prenatal exposure to phthalates on birth weight in neonates and the mediation effects of gestational age and pregnancy syndrome on the association between phthalate exposure and birth weight. Methods: In this study, 181 mother-newborn pairs were recruited from Wenzhou city. Maternal urine samples were collected during the third trimester and measured for phthalate metabolites by ESI-MS/MS. Structural equation models (SEMs) were used to evaluate effects of phthalate on birth weight controlling for maternal education, monthly income, nutritional supplements, infant gender, and maternal weight gain per week. The potential mediated effects of phthalate exposure through gestational age and pregnancy syndrome on birth weight were also calculated by structural equation modeling. Results: After adjusting for potential confounders, urinary mono-phthalate levels (including MMP, MBP, MEHP, MEOHP, and MEHHP) were negatively associated with birth weight. A ten-fold increase in the concentration of MEOHP and MEHHP would be directly associated with lower birth weights (reduced to 124 g and 107 g, respectively). However, MBP had mediated effects on birth weight through gestational age, which was associated with an 85-g reduction in birth weight for every ten-fold increase in exposure. Both direct and mediated effects on birth weight were found in MMP and MEHP. The indirect effects of MMP and MEHP were mediated through gestational age and pregnancy syndrome. Thus, prenatal MMP and MEHP exposures were associated with decrease in birth weight. Conclusions: A negative association exists between prenatal phthalate exposure and birth weight in Chinese neonates. In addition to direct pathway, phthalate exposures could affect birth weight through the mediated effects of gestational age and pregnancy syndrome.